An Oral History of the Special Olympics in China Volume 2 The Movement - Alford, William P.; Liao, Mei; Cui, Fengming (Economy and Social Inclusion, 2020)
This open access book contains the oral histories that were inspired by the work of the Special Olympics in conjunction with the 50th anniversary of its founding. The foreword and prefatory materials provide an overview of the Special Olympics and its growth in the People's Republic of China. The sections that follow record interview transcripts of individuals with intellectual disabilities living in Shanghai. In addition to chronicling the involvement of these individuals and their families in the Special Olympics movement, the interview transcripts also capture their daily lives and how they have navigated school and work.